Evidence for highly p-type doping and type II band alignment in large scale monolayer WSe2/Se-terminated GaAs heterojunction grown by molecular beam epitaxy. Issue 15 (1st April 2022) - Pierucci, Debora; Mahmoudi, Aymen; Silly, Mathieu; Bisti, Federico; Oehler, Fabrice; Patriarche, Gilles; Bonell, Frédéric; Marty, Alain; Vergnaud, Céline; Jamet, Matthieu; Boukari, Hervé; Lhuillier, Emmanuel; et al.
Abstract : Two-dimensional materials (2D) arranged in hybrid van der Waals (vdW) heterostructures provide a route toward the assembly of 2D and conventional III–V semiconductors. Abstract : Two-dimensional materials (2D) arranged in hybrid van der Waals (vdW) heterostructures provide a route toward the assembly of 2D and conventional III–V semiconductors. Here, we report the structural and electronic properties of single layer WSe2 grown by molecular beam epitaxy on Se-terminated GaAs(111)B. Reflection high-energy electron diffraction images exhibit sharp streaky features indicative of a high-quality WSe2 layer produced via vdW epitaxy. This is confirmed by in-plane X-ray diffraction. The single layer of WSe2 and the absence of interdiffusion at the interface are confirmed by high resolution X-ray photoemission spectroscopy and high-resolution transmission microscopy. Angle-resolved photoemission investigation revealed a well-defined WSe2 band dispersion and a high p-doping coming from the charge transfer between the WSe2 monolayer and the Se-terminated GaAs substrate. By comparing our results with local and hybrid functionals theoretical calculation, we find that the top of the valence band of the experimental heterostructure is close to the calculations for free standing single layer WSe2 . Our experiments demonstrate that the proximity of the Se-terminated GaAs substrate can significantly tune the electronic properties of WSe2 . The valence band maximum (VBM, located at the K point of the Brillouin zone) presents an upshift of about 0.56 eV toward the Fermi level with respect to the VBM of the WSe2 on graphene layer, which is indicative of high p-type doping and a key feature for applications in nanoelectronics and optoelectronics.